Karakter Morfologi dan Potensi Produksi Beberapa Aksesi Sagu (Metroxylon spp.) di Kabupaten Sorong Selatan, Papua Barat - Dewi, Ratih Kemala; Bintoro, Muhammad Hasyim; Sudradjat, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTSago palm is a carbohydrate source which has the highest carbohydrate content compared to the other crops. It can produce about 200-400 kg per trunk of sago dry starch. More than 50% sago palm population in the world are grown in Indonesia and 90% sago palm in Indonesia is found in Papua. This research was aimed to characterize several sago palm accessions in South Sorong District, West Papua. There were 12 accessions observed, i.e. Fasai, Fasampe, Falia, Fanomik, Fasongka, Fafion, Fakattao, Fanke, Fablen, Failik, Fakreit and Fasinan. Among these accessions, there were many differences based on morphological characteristics such as shoots color, crown shape, trunk height, number of leaf, existence of spine, starch content, also pith and starch color. Fablen was the only non-spiny type. Most of sago accessions were high yielding accessions with the potential yield more than 200 kg per trunk of sago dry starch. Fanomik had the highest potential yield. Sago palm productivity in the natural forest of Saifi Subdistrict, South Sorong District, West Papua was estimated to reach approximately 34.59 ton ha-1 per year of sago dry starch.   Keywords: accessions, starch, yield, food